Terapi Musik terhadap Nyeri Anak di Pediatric Intensive Care Unit - Kurniawati, Lilis; Allenidekania, Allenidekania; Nurhaeni, Nani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the benefits of music therapy intervention on pain experienced by children treated in the Pediatric Intensive Care Unit (PICU). The method used is through searching for articles adapted to the formulation of research questions using the PICO formula in the EMBASE, Clinicalkey for Nursing, Proquest, ScienceDirect, Springer Link, Pubmed, and Scopus databases. The research results showed that music therapy for children treated in the PICU varied, including live music therapy, recorded music therapy, music therapy and hand massage, and music and video therapy. In conclusion, intervention through music therapy has proven to be effective in reducing pain, increasing comfort, and stabilizing children's hemodynamics. Keywords: Children, Pain, Pediatric Intensive Care Unit, Music Therapy